2015
DOI: 10.1515/rjdnmd-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin Dosage Value as A Diagnostic and Postoperative Marker in Diabetic Patients with Colorectal Cancer

Abstract: Background and Aims: We evaluated fecal calprotectin values in patients with colorectal neoplasms undergoing surgery, comparatively in patients with and without diabetes mellitus. Material and Methods: We studied 40 patients operated for colorectal neoplasm, divided into two groups: one group of 20 patients with insulin-treated type 2 diabetes and another group of 20 patients without diabetes. Results: Patients had a high percentage of preoperative calprotectin test positivity (90%, 36 patients). A total of 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Kristinsson et al [ 23 ] found that median FC fell significantly from 75 to 10.3 mg/l, after resection. This has again been shown by Kristinsson et al [ 16 ], Lehman et al [ 42 ], and Borza et al [ 44 ]. Despite the lack of evidence supporting the use of FC in screening, this is evidence to show that FC is related to intraluminal tumour burden, and hence may be relevant to clinical diagnosis, pre-operative CRC staging and cancer follow-up.…”
Section: Discussionsupporting
confidence: 74%
“…Kristinsson et al [ 23 ] found that median FC fell significantly from 75 to 10.3 mg/l, after resection. This has again been shown by Kristinsson et al [ 16 ], Lehman et al [ 42 ], and Borza et al [ 44 ]. Despite the lack of evidence supporting the use of FC in screening, this is evidence to show that FC is related to intraluminal tumour burden, and hence may be relevant to clinical diagnosis, pre-operative CRC staging and cancer follow-up.…”
Section: Discussionsupporting
confidence: 74%